1994
DOI: 10.2136/sssaj1994.03615995005800050032x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration Characteristics under No‐Till and Clean‐Till Furrow Irrigation

Abstract: Tillage or the lack of tillage affects infiltration and its variability across the field. To quantify infiltration characteristics of soil under no‐till and clean‐till furrow irrigated systems, a 3‐yr rotation of wheat (Tritium aestivum L.)‐sorghum [Sorghum bicolor (L.) Moench]‐fallow on a Pullman sandy clay loam soil (fine, mixed, thermic Torrentic Paleustoll) was initiated. Treatments were no‐till and clean‐till with or without wheel traffic. Soil water contents, water advance times down the furrow, wetted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The effect of tillage on water infiltration was still considered to be positive; however, these results suggest that excessive tillage may reduce infiltration through the effect on hydraulic conductivity. Christensen et al (1994) found that more soil water was conserved during fallow periods with no tillage than with clean till, and in contrast to Creswell et al (1993), the infiltration rates were larger with no tillage as evidenced by the slow rate of the advance of water down irrigation furrows. They reported that sorghum [ Sorghum bicolor (L.) Moench] grain yields were higher with no tillage, but wheat yields were less with clean‐till.…”
Section: Soil Surface Modificationsmentioning
confidence: 66%
“…The effect of tillage on water infiltration was still considered to be positive; however, these results suggest that excessive tillage may reduce infiltration through the effect on hydraulic conductivity. Christensen et al (1994) found that more soil water was conserved during fallow periods with no tillage than with clean till, and in contrast to Creswell et al (1993), the infiltration rates were larger with no tillage as evidenced by the slow rate of the advance of water down irrigation furrows. They reported that sorghum [ Sorghum bicolor (L.) Moench] grain yields were higher with no tillage, but wheat yields were less with clean‐till.…”
Section: Soil Surface Modificationsmentioning
confidence: 66%
“…Practically, farmers have adopted field management approaches such as reduced or zero tillage that help to mitigate the adverse impact of climate change [66]. More soil water is conserved in summer fallow under reduced tillage compared with conventional tillage methods [66,67]. New crop cultivars with improved shoot and root architecture would promote the effective capture and utilization of solar radiation, carbon dioxide, and rain and soil stored water; thus, they are recommended to cope with climate change [68,69].…”
Section: Factors Influencing Wfsmentioning
confidence: 99%
“…Tillage is considered to have a positive impact on water infi ltration, but excessive tillage may reduce infi ltration because of the direct eff ect on hydraulic conductivity. Christensen et al (1994) observed that soil water was conserved during fallow periods with no-tillage compared to clean-till, and his fi ndings were opposite of those found by Cresswell et al (1993). They found sorghum [Sorghum bicolor (L.) Moench] grain yields to be increased with adoption of no-tillage because water was conserved during the fallow periods accompanied with a deeper wett ing of the soil profi le in notillage systems.…”
Section: Tillagementioning
confidence: 89%